Readiness assessment for implementing industry 4.0: A case study at an aerospace manufacturing company - Abd Aziz, Noor Zuhaira (2024)
The aerospace is one of the industries that has great capabilities and is continually striving to come up with innovations. In the context of impacts of the Fourth Industrial Revolution (IR 4. 0), there is a need to evaluate the level of readiness of organization within this industry. This study aims to examine the readiness of an aerospace manufacturing company in Malaysia toward IR 4.0. The problem addressed under consideration is lack of research on the topic related to the readiness, particularly aerospace manufacturing industry, for IR 4. 0 adoption. The methodology employed involves a comprehensive readiness assessment using the IMPULS model, which evaluates dimensions. The added dimensions to it combine strategy and organization, employees, smart factory, smart operation, data-driven services, cost and financial and customer aspects. Information from the questionnaire was utilized to analyze the relationship constructs and validated through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). In the same respect, the Fuzzy Delphi Method (FDM) was employed to categorize the barriers and drivers essential to IR 4. The findings based on the relationship significance showed that strategy and organization, and cost and financial aspects, as well as employees leave a significant impact on IR 4. 0 readiness. The FDM results highlighted critical barriers such as the shortage of capable training providers and low digital readiness and connectivity, while drivers included higher operational efficiency and the growth of market and new markets. The results show a moderate level of readiness at level three (3). The company scored higher in strategy and organization (SO) and employee readiness (EMP), indicating strong strategic planning and a well-prepared workforce. However, there are significant gaps in smart operations and data-driven services that need substantial improvement. The conclusion drawn is that while the company demonstrates potential for adopting IR 4.0 technologies, focused efforts are needed to address specific dimensions to enhance overall readiness.